Phytohormones on the germination and initial growth of pumpkin seedlings under different types of water - Keylan S. Guirra; Salvador B. Torres; Moadir de S. Leite; Bruno S. Guirra; Francisco A. Nogueira Neto; Anna L. B. Rêgo (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Pumpkin (Curcubita moschata Duchesne) production in quantity and quality is often restricted due to adverse environmental conditions. Thus, the objective was to evaluate the action of phytohormones as stress attenuators on the germination and initial growth of pumpkin seedlings, cv. Sergipana, under different types of water. The design adopted was completely randomized, in a 3 × 4 factorial scheme, with four repetitions. In addition to the control, the seeds were treated with the gibberellic and salicylic acids and irrigated with the supply water, fish farming wastewater, artesian well water and solution of the mixture of fish farming wastewater + artesian well water, in a 1:1 ratio. The variables evaluated were germination, first germination count, germination speed index, length of shoots and roots, dry mass of shoots and roots, soluble sugars, amino acids and proline. Treatment of pumpkin seeds, cv. Sergipana, with gibberellic and salicylic acids improved germination kinetics and attenuated the effects of water salinity during the initial growth of pumpkin seedlings.